Examining longitudinal associations between the recreational physical activity environment, change in body mass index, and obesity by age in 8864 Yorkshire Health Study participants. (April 2019) - Hobbs, M.; Griffiths, C.; Green, M.A.; Christensen, A.; McKenna, J.
Abstract: The environment may lead to lower body mass index (BMI) and obesity risk by providing opportunities to be physically active. However, while intuitively appealing, associations are often inconsistent in direction and small scale. This longitudinal study examined if change in BMI and obesity was associated with the availability of physical activity (PA) facilities and parks and explored if these associations differed by age. Longitudinal data (n = 8, 864, aged 18–86 years) were provided at baseline (wave I: 2010–2012) and follow up (wave II: 2013–2015) of the Yorkshire Health Study. BMI was calculated using self-reported height (cm) and weight (kg) (obesity = BMI≥30.00). To define availability, home addresses were geocoded based on postcode zone centroids and neighbourhood was defined as a 2 km radial buffer. PA facilities were sourced from Ordnance Survey Points of Interest (PoI) and parks were sourced from OpenStreetMap. Environmental data temporally matched individual-level baseline data collection. PA facilities (b = −0.006 [-0.015, 0.003]) and parks (b = −0.001 [-0.015, 0.013]) at baseline were not associated with change in BMI. Change in obesity was unrelated to parks (OR = 0.994 [0.975, 1.015]) and while PA facilities were related (OR = 0.979 [0.965, 0.993]), effects were small. A combined measure of the recreational PA environment including parks and PA facilities was unrelated to change in BMI and obesity. Despite this, statistically significant interactions were found for both PA facilities, parks, and change in obesity by age. Based on the premise that an individual's mobility varies with age, and although effects were small, this offers tentative evidence which suggests it may be useful for policymakers in Public Health and Planning to consider the impact of environmental interventions across the life course. Highlights: Recreational physical activity environments (RPE) may be related to BMI and obesity. In this study, the RPE was not related to change in BMI or obesity. The relationship between the RPE, change in BMI and obesity differs by age. It may help policy to consider environmental interventions across the life course.